Movement of Fertilizer Pieces on the Braker Drum of a Device that Installes Organo-Mineral Fertilizer Compounds on a Single Way During Pillowing, Theoretical Study - Tukhtaquziev, Abdusalim; Bakhodirova, Samsakova Khilola (American Journal of Biodiversity, 2025)
The results of studies conducted on the theoretical study of the movement of fertilizer particles in the paddle drum of a device that provides local application of a mixture of organo-mineral fertilizers to the soil layer where plant roots develop during ridge formation are presented. According to the results of the conducted studies, at a blade length of 6 cm, the fertilizer transfer time was 0.135 seconds, and the transfer rate was 0.885 m/s.